Acute Toxicity Test of Gedi (Abelmoschus manihot L.) Ethanol Leaves Extract to Histopatology of Liver Mice - Mutmainna Mutmainna; Yenti Purnamasari; Parawansah Parawansah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACTBackground: Abelmoschus manihot L.are widely used  as a daily dish  of dishes and traditional medicine to treat various diseases. It contains alkaloids, triterpenoids, saponins, and flavonoids wich can be toxic agent at variable dose. Purpose: This study aimed determine the effect of ethanol extract of abelmoschus manihot L. on histopatologic image of mice liver tissue.  Methods: This is quasi experimental study  with post test only control group design. Fourty five mice  (mus musculus)  as the subject of this research, they divided into 5 groups, group I threated by 50 mg /kgBB extract, group II threated by 200 mg / kgBB extract, group III threated by 800 mg / kgBB extract, group IV threated by 3,200 mg / kgBB extract, and group V as negative control. Treatment was done for 14 days and terminated at next day for histopatology examination use them liver tissue. Result: Histopathological examination of liver cells within normal limits. In the treatment group of 50 mg liver tissue of mice who died during treatment on day 7 and day 10 showed liver tissue necrosis. In the treatment group of 200 mg and 800 mg of liver tissue showed the presence of liver cell necrosis, and cell boundaries appeared unclear. In the treatment group of 3200 mg liver tissue showed necrotic cells, lysi s cells, unclear  cell  boundaries  and  necrotic  cells  more  widely.Conclusion:  As  a  conclusion  there  an histopatologic changes of  microscopic examination of mice liver cells in the form of necrosis and, there is not significant difference in ALT and AST  between the control group.Keywords : Abelmoschus manihot L. extract, acute toxicity, liver histopathology